Fire force : the hero and the princess - Ohkubo, Atsushi (Tokyo : Kodansha Comics, 2016)
The city of Tokyo is plagued by a deadly phenomenon: spontaneous human combustion! Luckily, a special team is there to quench the inferno: The Fire Force! The fire soldiers at Special Fire Cathedral 8 are about to get a unique addition. Enter Shinra, a boy who possesses the power to run at the speed of a rocket, leaving behind the famous 'devil's footprints' (and destroying his shoes in the process). Can Shinra and his cooleagues discover the source of this strange epidemic before the city burns to ashes?
VOL 3
Keywords: Science fiction